Finlay Donovan digs her own grave - Cosimano, Elle (Cosimano, Elle. Finlay Donovan series., 2025)
"From New York Times bestseller and Edgar-Award nominee Elle Cosimano, comes Finlay Donovan Digs Her Own Grave-the hugely anticipated next installment in the fan-favorite Finlay Donovan series. Finlay Donovan may have skeletons in her closet . . . but at least there's not a body in her backyard. Finlay Donovan and her nanny/partner-in-crime, Vero, have not always gotten along with Finlay's elderly neighbor, Mrs. Haggerty, the community busybody and president of the neighborhood watch. But when a dead body is discovered in her backyard, Mrs. Haggerty needs their help. At first a suspect, Mrs. Haggerty is cleared by the police, but her house remains an active crime scene. She has nowhere to go . . . except Finlay's house, right across the street. Finlay and Vero have no interest in getting involved in another murder case-or sacrificing either of their bedrooms. After all, they've dealt with enough murders over the last four months to last a lifetime and they both would much rather share their beds with someone else. When the focus of the investigation widens to include Finlay's ex-husband, Steven, though, Finlay and Vero are left with little choice but to get closer to Mrs. Haggerty and uncover her secrets . . . before the police start digging up theirs. But who will solve the mystery first?"--